The reuse of texts in Finnish newspapers and journals, 1771–1920: A digital humanities perspective. Issue 1 (29th October 2020) - Salmi, Hannu; Paju, Petri; Rantala, Heli; Nivala, Asko; Vesanto, Aleksi; Ginter, Filip
Abstract: The digital collections of newspapers have given rise to a growing interest in studying them with computational methods. This article contributes to this discussion by presenting a method for detecting text reuse in a large corpus of digitized texts. Empirically, the article is based on the corpus of newspapers and journals from the collection of the National Library of Finland. Often, digitized repositories offer only partial views of what actually was published in printed form. The Finnish collection is unique, however, since it covers all published issues up to the year 1920. This article has a two-fold objective: methodologically, it explores how computational methods can be developed so that text reuse can be effectively identified; empirically, the article concentrates on how the circulation of texts developed in Finland from the late eighteenth century to the early twentieth century and what this reveals about the transformation of public discourse in Finland. According to our results, the reuse of texts was an integral part of the press throughout the studied period, which, on the other hand, was part of a wider transnational practice.